Sustainability as a Competitive Advantage: Branding and Marketing Green Hospitality - George, Sindhu (Ushus Journal of Business Management, 2025)
In today's world, where people are more conscious about the environment, making eco-friendly choices impacts consumer’s buying behaviour, especially in the hospitality sector. The individual choices for preferring a product based on how the company is giving priority for the sustainability. It seeks to define how green branding and marketing can create trust and loyalty and with it enhance competitive advantage. This study uses data gathered through a structured questionnaire from 100 hotel customers in India. It employs Structural Equation Modeling (SEM) through WarpPLS 7.0 to assess the association between green image, green trust, green satisfaction, and green loyalty. The findings suggest that green image and green trust positively influence green satisfaction while green satisfaction enhances green loyalty. The paper underlines the marketing importance of sustainable branding for hotels and provides strategies for elevating consumers green satisfaction and loyalty to genuine green image and trust of the product.